Cardiac magnetic resonance to predict recurrences after ventricular tachycardia ablation: septal involvement, transmural channels, and left ventricular mass. Issue 9 (18th June 2021) - Quinto, Levio; Sanchez, Paula; Alarcón, Francisco; Garre, Paz; Zaraket, Fatima; Prat-Gonzalez, Susana; Ortiz-Perez, Jose T; JesúsPerea, Rosario; Guasch, Eduard; Tolosana, José Maria; San Antonio, Rodolfo; Arbelo, Elena; et al.
Abstract: Aims: Ventricular tachycardia (VT) substrate-based ablation has an increasing role in patients with structural heart disease-related VT. VT is linked to re-entry in relation to myocardial scarring with areas of conduction block (core scar) and areas of slow conduction [border zone (BZ)]. VT substrate can be analysed by late gadolinium enhancement cardiac magnetic resonance (LGE-CMR). Our study aims to analyse the role of LGE-CMR in identifying predictors of VT recurrence after ablation. Methods and results: We analysed 110 consecutive patients who underwent VT ablation from 2013 to 2018. All patients underwent a preprocedural LGE-CMR, and in 94 patients (85.5%), the CMR was used to aid the ablation. All LGE-CMR images were semi-automatically processed using dedicated software to detect scarring and conducting channels. After a median follow-up of 2.7 ± 1.6 years, the overall VT recurrence was 41.8% with an implantable cardioverter-defibrillator shock reduction from 43.6% to 28.2% before and after ablation, respectively. The amount of BZ (26.6 ± 13.9 vs. 19.6 ± 9.7 g, P  = 0.012), the total amount of scarring (37.1 ± 18.2 vs. 29 ± 16.3 g, P  = 0, 033), and left ventricular (LV) mass (168.3 ± 53.3 vs. 152.3 ± 46.4 g, P  < 0.001) were associated with VT recurrence. LGE septal distribution [62.5% vs. 37.8%; hazard ratio (HR) 1.67 (1.02–3.93), P  = 0.044], channels with transmural path [66.7% vs. 31.4%, HR 3.25 (1.70–6.23), P  < 0.001], and midmural channels [54.3% vs. 27.6%, HR 2.49 (1.21–5.13), P  = 0.013] were related with VT recurrence. Multivariate analysis showed that the presence of septal LGE [HR 3.67 (1.60–8.38), P  = 0.002], transmural channels [HR 2.32 (1.15–4.72), P  = 0.019], and LV mass [HR 1.01 (1.005–1.019), P  = 0.002] were independent predictors of VT recurrence. Conclusion: Pre-procedural LGE-CMR is a helpful and feasible technique to identify patients with high risk of VT recurrence after ablation. LV mass, septal LGE distribution, and transmural channels were predictive factors of post-ablation VT recurrence.